REDEMPTION OF THE MAIN CHARACTER IN THE NOVEL “THE KITE RUNNER” BY KHALED HOSSEINI (A GENETIC STRUCTURALISM APPROACH) - Sitti Aglitasia Merdekawati; Fachmi Alhadar; Nurfani Nurfani (UIN Alauddin Makassar, 2017)
AbstractThis research aims at to identify actions that reflect redemption. In addition, the other objective in it is to identify the factors cause redemption of the main character. The novel